Synthesis of Hematite Pigment (A-Fe2O3) from Iron Lathe Waste using Precipitation-Sonication Method as Anti-Swelling on Wood - Rahmawati, Dewi Elok; Khoiroh, Lilik Miftahul; Ningsih, Rachmawati; Yusniyanti, Febi; Solawati, Wariatus; Sari, Puspa (International Journal of Mechanical Engineering Technologies and Applications, 2020)
Iron lathe waste powder has the potential as a raw material in the synthesis of hematite pigments. Hematite pigments have many advantages, one of which is anti-swelling properties that can maintain the dimensions of wood. Hematite pigment synthesis was carried out using the precipitation-sonication method. The precipitation stage uses an ammonium hydroxide solution as a precipitating agent. Stages of sonication using the PEG-6000 template were performed at different times were 30, 45, and 90 minutes then calcined at 750 Â° C for 3 hours. The samples were characterized by X-ray diffraction (XRD), color reader, and scanning electron microscope-energy dispersive X-Ray (SEM-EDX). The result confirmed that a ferrihydrite phase obtained after the precipitation process and transform into hematite after the calcination process with the highest degree of crystallinity for 90-minute sonication. From a color reader, the brightness and redness degrees decrease with increasing time. Scanning electron microscope results illustrated that the morphology was not uniform with the particle size getting smaller with increasing sonication time. The EDX results show that hematite pigments still contain impurities such as carbon. The swelling test indicated that the highest stability in hematite-pigmented wood increased as increasing in the weight of pigment.